2022
DOI: 10.1111/bju.15858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluid absorption during flexible ureteroscopy in an in vivo porcine model

Abstract: Objective To evaluate the relationship between renal pelvis pressure and fluid absorption during ureteroscopy (URS) in a live porcine model. Materials and Methods Flexible URS (fURS) was performed in anaesthetised female Yorkshire pigs. Prior to performing fURS, a 0.3556‐mm (0.014″) pressure‐sensing guidewire (Comet™, Boston Scientific) was placed to monitor renal pelvis pressure. A simulated fURS procedure was then performed for 1 h. Infusion of irrigation fluid (5% ethanol in saline) at target renal pelvis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Manual gravity-based method with a low level of irrigation pressure results in lower IRPs compared to automatic pumps and high irrigation pressure [20]. In vitro studies often required porcine model, but the living or deceased porcine urinary tract elasticity has never been compared to human upper urinary tract [17,18,21,26]. Therefore, exporting the in vitro results to clinical practice appears difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Manual gravity-based method with a low level of irrigation pressure results in lower IRPs compared to automatic pumps and high irrigation pressure [20]. In vitro studies often required porcine model, but the living or deceased porcine urinary tract elasticity has never been compared to human upper urinary tract [17,18,21,26]. Therefore, exporting the in vitro results to clinical practice appears difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fluid absorption risk during fURS, at 50mmHg, 30% of cases presented fluid penetration from calyx to renal capsule, with a significant decrease using UAS [21]. Kottooran et al evaluated the amount of absorbed fluid after 1 h fURS: 7.6, 10.8, 26.0, and 56.8 ml at renal pelvis pressures of 37, 55, 75, and 150 mmHg, respectively [26]. As a solution to IRP increase during fURS, several devices are under evaluation: new UAS and robotic system [24,25,27].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The data also indicated that elevated renal pelvic pressure during URS demonstrated a positive association with increased uid absorption. 11 These outcomes offer valuable insights into uid dynamics throughout URS procedures, thereby facilitating informed clinical decision-making in managing urinary stone disease.…”
Section: Discussionmentioning
confidence: 99%